Organizing Love - Thoughts on the Transformative and Activist Potential of Feminine Writing - Vachhani, Sheena J. (Gender, work, and organization, 2015)
This paper engages with what it means to write love and poses the question: what does love do for feminine writing? I move beyond the concept of love as an ideology or condition of work (such as ‘for the love of the job’) and draw on a feminine poetics of organization that highlights its disruptive potential. Love, in this sense, breaks the rationality and order of the ‘masterful’ text and alters gendered academic writing. The power of writing with love and effecting change in organizations is developed through a discussion of three feminist writers. The paper explores three significant texts, Kristeva's Tales of Love; Irigaray's The Way of Love; and hooks’ All About Love, in order to examine the problematic representation of love and to advocate a turn to an ethics of love as a basis for self‐other relations that points us to defiant, activist and transformative forms of feminine writing. These writers bring to bear practical politics and possibilities through political interruption — namely through three modes: reconstruction, reclamation and activation, and I discuss the implications of these modes for work and organization, notably that writing and thinking the wisdom of love offers insight into how we creatively imagine socially just organizations of the future. © 2015 John Wiley & Sons Ltd